The Role of Toll-Like Receptor in Inflammation and Tumor Immunity - Xiaohong Cen; Shuwen Liu; Kui Cheng (2018)
Toll-like receptors (TLRs) activation enable host to recognize a large number of pathogen-associated molecule patterns (PAMPs), and ignite immune cells to discriminate between self and non-self, then promote the following innate and adaptive immune response. Accumulated clinical/preclinical evidences have proven TLRs to be critical role in the autoimmune diseases, including inflammatory and tumor-associated diseases. Activation of TLRs has been or is becoming a target for cancer treatment. It is shown that TLR can induce preferable anti-tumor effect by eliciting inflammatory cytokines expression and cytotoxic T lymphocytes (CTLs) response. As adjuvant, TLR agonists can launch a strong immune response to supply the insufficiency of both cancer radiotherapy and bio-chemotherapy. On the other hand, tumor-associated antigen acting as PAMPs, can also activate TLRs and induce tumor gene-related programmed cell death, including apoptosis, autophagy and programmed necrosis. While there are also argument that the excessive TLR expression will promote the tumor deterioration in various organisms, as the TLR-induced inflammation will accelerate the cancer cells boost in the tumor microenvironment. However, the effect of TLRs acting on cancers is still not quite clear today. In this review, we will summarize recent researches of TLR in cancer treatment and their role in tumor microenvironment, giving a brief overview on future expectation.